Open-Circuit Voltage Characteristics of Cu–Zn Soil Batteries in Humus, Peat, and Sand: Experimental Comparison and Empirical Regression - suwandi, suwandi; Utami, Amaliyah Rohsari Indah; Fitriyanti, Nurwulan; Davianti, Ajeng Faradilla Putri; Ghassani, Deika Saffanah Nisyyah; Arfandi, Rizky Nurfadillah (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
The development of low-cost, sustainable power sources is critical to supporting distributed environmental sensing, agricultural monitoring, and physics education in regions with limited or unreliable access to the grid. This study investigates the open-circuit voltage (OCV) characteristics of Cu–Zn soil batteries embedded in three representative Indonesian soils, humus, peat, and sand, using a 26-cell series–parallel stack under controlled laboratory conditions, along with an empirical logarithmic regression model for electrode sizing. A total of 26 Cu–Zn cells were installed in each soil type, with three independent containers per soil (n = 3) at 25 ± 1 °C; stack OCV was recorded every 5 minutes over 30 minutes, and baseline soil physicochemical properties (moisture, pH, organic C, total N, C/N ratio, and exchangeable Ca, K, and Fe) were characterized to aid interpretation. The results show that humus produced the highest and most stable average stack voltage (9.92 V; range 9.55–10.08 V), followed by peat (8.70 V; 8.50–8.90 V) and sand (6.17 V; 5.99–6.27 V), a ranking consistent with differences in organic matter, acidity, and exchangeable cations rather than directly measured soil electrical conductivity. An empirical logarithmic model linking electrode surface area to OCV, adapted from previous studies and recalibrated for the present configuration, yielded average relative errors of approximately 4–5% within the tested electrode-area range, indicating good agreement between predicted and measured voltages while remaining well below theoretical electrochemical potentials. Within the limitations of short-term, open-circuit measurements without current–voltage or aging tests, these findings identify humus as the most favorable medium among the tested soils for achieving relatively high and stable OCV, and provide an empirically validated framework to support the design and upscaling of Cu–Zn soil battery arrays for sustainable low-power applications in agriculture and physics education.